2018
DOI: 10.5505/pajes.2016.70048
|View full text |Cite
|
Sign up to set email alerts
|

Production of block by using fly ash, lime and glass powder

Abstract: (Kalsiyum-Alüminat-Kalsiyum-Sülfat-Hidrat)Portland çimentosuz, salt uçucu külden blok ya da briket üretimiyle ilgili sınırlı sayıda çalışma yapılmıştır. Berry ve diğ.[3] sadece C sınıfı uçucu kül kullanarak beton üretmiş ve ürettikleri betonun yapısal performansının iyi olduğunu belirtmişlerdir. , C sınıfı uçucu kül-kalker tozu, uçucu kül-kalker tozu-silis dumanı ve uçucu kül-kalker tozucam tozu kullanarak üç farklı yığma yapı bloku üretmiştir. Blokların üretiminde şu yol izlenmiştir; karışımı oluşturan toz ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The consistency of the mixtures in which EP is substituted by 6% and the control mixtures without EP are very close to each other, and an increase in the water requirement was observed when the replacement ratio increased to 18%. Since calcite has a hydrophobic characteristic (Turgut, 2018;Turgut and Ogretmen, 2019;Demirhan, 2020), a partial decrease in consistency has been observed with the use of both nano and micronized calcite.…”
Section: Consistencymentioning
confidence: 99%
“…The consistency of the mixtures in which EP is substituted by 6% and the control mixtures without EP are very close to each other, and an increase in the water requirement was observed when the replacement ratio increased to 18%. Since calcite has a hydrophobic characteristic (Turgut, 2018;Turgut and Ogretmen, 2019;Demirhan, 2020), a partial decrease in consistency has been observed with the use of both nano and micronized calcite.…”
Section: Consistencymentioning
confidence: 99%
“…Average results found via Vicat Test Method are given in Figure 3.1. As seen in the Figure, test results showed that although nanomaterials are expected to increase the water requirement due to their high specific surface area, as the usage rate of NC increases, the water requirement needed for standard consistency has decreased due to the hydrophobic structure of NC (Lu and Wang 2010;Turgut 2018;Turgut 2019;Demirhan et al 2019). Fly ash which is finer than cement has increased the water demand required for standard consistency as fly ash replacement level increased.…”
Section: Setting Timesmentioning
confidence: 99%